Referenciação e interpretação: uma proposta de atividade com descritores de língua portuguesa do SAEB - 9o ano-ensino fundamental - anos finais - Ferreira, Virgínia de Fátima da Silva (2023)
Under the perspective of Text Linguistics, this research aims to establish relations between the SAEB descriptors and the presuppositions of referentiation, in order to propose a set of activi- ties of comprehension of the texts compiled in a didactic-pedagogical notebook that help teach- ers in the Portuguese language classes. This research finds its theoretical support in the studies of Text Linguistics (TL), especially regarding the reflections on referentiation (Cavalcante, 2010; Cavalcante; Lima,2012; Cavalcante; Custódio; Brito,2014; Matos, 2018) as well as the notion of discursive topic (Jubran,2006; Marcuschi, 2008; Cavalcante, 2010; Sá, 2018). From this basis, we make a dialogue with discourse analysts, more especially the scholars who work with the conception of argumentativeness (Amossy, 2020) and, above all, with text linguists, such as Cavalcante and Brito (2020) and Koch and Elias (2016). Such articulation between text and discourse is supported by the presuppositions of Cavalcante and Custódio Filho (2010), for whom the approach of the text in a sociocognitive-discursive perspective contributes to the dialogue with other areas of knowledge. Along with this theoretical support, the work was methodologically structured in the following steps: survey on the general performance of the students in the applications of the SAEB Assessment; study of the referential processes, in order to propose a relation between them and the descriptors D1, D2, D3, D4, D6, D5 and, D18; proposition of a set of interpretation activities in a didactic-pedagogical notebook, which con- templates 20h/a with pedagogical orientations for the teachers. As the didactic-pedagogical notebook elaborated by us, has not yet been used by the target audience (students of the 9th grade of elementary school-final years), it is not yet possible to compare objective considera- tions about results achieved, at the current moment, however we aim, with this work, to effec- tively contribute to the development of the students’ interpretation so that they can be able to exercise, through language, the role of critical and responsible citizens in the society in which they act.”